2021
DOI: 10.3856/vol49-issue4-fulltext-2673
|View full text |Cite
|
Sign up to set email alerts
|

Histological structure of the digestive tract and digestive enzymatic activity of juvenile Pacific seahorse (Hippocampus ingens)

Abstract: The histological structure, histochemical features, and enzymatic activity of the digestive tract of juvenile Pacific seahorse (Hippocampus ingens) are described to provide information during the cultivation of this species. Serial histological sections were stained with either hematoxylin-eosin, alcian blue-PAS, toluidine blue, Sudan black, Masson's trichome, and ninhydrin-Schiff to describe the general features and the presence of glycogen, mucopolysaccharides, lipids, muscle layers, and proteins, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Respondents gave no information regarding the survival rate of newborns. It has been reported that seahorses do not have a larval phase and are born as miniature adults that only grow in size and modify their external morphology according to habitat conditions and feeding (Corona-Rojas et al 2021; Encomendero et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Respondents gave no information regarding the survival rate of newborns. It has been reported that seahorses do not have a larval phase and are born as miniature adults that only grow in size and modify their external morphology according to habitat conditions and feeding (Corona-Rojas et al 2021; Encomendero et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Hippocampus ingens "caballito de mar", es un pez que presenta muchas características estructurales que son adaptaciones para su estilo de vida acuática, además los conteos y mediciones destacan la necesidad de buscar características morfológicas que avalen las diferencias establecidas y pueden ayudar a diferenciar la especie de Hippocampus endémica y característica de nuestro litoral (Corona-Rojas, 2015;Corona-Rojas et al, 2021).…”
Section: Introductionunclassified